Comparative Diversity of Bats in Two Contrasting Habitats in Terengganu - BASRI, HASRULZAMAN HASSAN; MOHAMED, NOR ZALIPAH; SHAFIE, NUR JULIANI; ABDULLAH, MOHD. TAJUDDIN (Borneo Journal of Resource Science and Technology, 2022)
Differentiations in the habitat and resource utilisation lead to segregation and specialisation of niches for bats within the structurally complex tropical rainforest in Malaysia. This research aims to characterise chiropterans’ assemblages found in two different habitat types in Tasik Kenyir (dipterocarp forest) and Setiu (oil palm plantation). A total of 48 sampling nights were conducted within two years period from March 2017 to March 2019 which covered four sampling sites in Tasik Kenyir and four sites at Setiu. Two standard four-bank harp traps and 10 mist nets were deployed throughout the study at every site to capture bats at understory levels. This makes a total of 576 sampling efforts for both areas. Song Meter SM2bats and Echo Meter Touch from Wildlife Acoustic were used to record the echolocation of insectivorous bats. The total number of individuals and species observed were used to determine species diversity, richness, and evenness. Paleontological statistic software was used to generate the rank abundance and species accumulation curves. Bray-Curtis similarity index was used to generalise the index that represents the relative abundance of the sampling sites. A total of 835 individuals comprising 31 species from six families were captured at both study areas. Out of 835 individuals, 695 were captured within Tasik Kenyir comprising 27 species from six families (H = 2.381) while 140 individuals were captured in Setiu comprising 20 species from five families (H = 2.40). The diversity of bats in Tasik Kenyir was hypothesised to be higher than in Setiu as the habitat possess a larger undisturbed forest. However, the result showed the opposite in which no significant difference was detected from the diversity index calculated between these two areas. Detailed studies need to be conducted to determine if some areas are used as transient habitats for bats.